The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27030704
|View full text |Cite
|
Sign up to set email alerts
|

The System Profile of Renal Drug Transporters in Tubulointerstitial Fibrosis Model and Consequent Effect on Pharmacokinetics

Abstract: With the widespread clinical use of drug combinations, the incidence of drug–drug interactions (DDI) has significantly increased, accompanied by a variety of adverse reactions. Drug transporters play an important role in the development of DDI by affecting the elimination process of drugs in vivo, especially in the pathological state. Tubulointerstitial fibrosis (TIF) is an inevitable pathway in the progression of chronic kidney disease (CKD) to end-stage renal disease. Here, the dynamic expression changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Western blot analysis was performed to evaluate the expression of drug resistance-related proteins caused by the different treatments. We found that free CDDP exhibited no significant effect on MDR1 expression, resulting in multidrug resistance. Free Nira, MCT, and MNT moderately reduced MDR1 expression, and the effect of MNCT was the most significant owing to the synergistic effect of Nira. In the SKOV3 DDP cells, the drug-loaded NPs exhibited a higher decrease in MDR1 expression than the single free drugs.…”
Section: Resultsmentioning
confidence: 82%
“…Western blot analysis was performed to evaluate the expression of drug resistance-related proteins caused by the different treatments. We found that free CDDP exhibited no significant effect on MDR1 expression, resulting in multidrug resistance. Free Nira, MCT, and MNT moderately reduced MDR1 expression, and the effect of MNCT was the most significant owing to the synergistic effect of Nira. In the SKOV3 DDP cells, the drug-loaded NPs exhibited a higher decrease in MDR1 expression than the single free drugs.…”
Section: Resultsmentioning
confidence: 82%